Oxidative decolorization of carmosine with acidic chloramine-T: Spectrophotometric, kinetic and mechanistic chemistry - Shubha, Jayachamarajapura Pranesh; Puttaswamy, Puttaswamy (European Journal of Chemistry, 2012)
Carmosine is mainly used as a colorant in food industries. The oxidative decolorization of this dye is of greater significance and understanding of its kinetic and mechanistic aspects in redox reactions is important. Chloramine-T bears diverse chemical properties and has been exploited as oxidant for a variety of substrates. It is commercially available, inexpensive, non toxic, water tolerant and easy to handle. A systematic kinetic study of the oxidation of carmosine with acidic chloramine-T (CAT: TsNClNa here Ts = CH3C6H4SO2-) has been carried out in order to explore the mechanistic aspects of this redox system. UV-Visible spectrophotometry is used to monitor the reaction. Optimum conditions for the oxidative decolorization of carmosine with CAT were established. The kinetic results revealed that the reaction rate exhibits a first-order dependence each on [CAT]o and [carmosine]o and less than unit order dependence on [H+]. The reaction rate was examined for the effects of (a) p-toluenesulfonamide, (b) halide ions, (c) ionic strength, (d) dielectric permittivity and (e) solvent isotope. The reaction was studied at different temperatures and the activation parameters have been deduced. Oxidation products were characterized. Test for free radicals was found to be negative. The derived rate law based on the proposed mechanism is in complete agreement with the observed kinetic data.